If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3m = 16 + 2m Solving 6 + -3m = 16 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 6 + -3m + -2m = 16 + 2m + -2m Combine like terms: -3m + -2m = -5m 6 + -5m = 16 + 2m + -2m Combine like terms: 2m + -2m = 0 6 + -5m = 16 + 0 6 + -5m = 16 Add '-6' to each side of the equation. 6 + -6 + -5m = 16 + -6 Combine like terms: 6 + -6 = 0 0 + -5m = 16 + -6 -5m = 16 + -6 Combine like terms: 16 + -6 = 10 -5m = 10 Divide each side by '-5'. m = -2 Simplifying m = -2
| 5x-(2-x)=22 | | 150m-75m+48000=50000-175m | | 3(n+.333)=2 | | 200m-125m+47750=50500+175m | | 3x^2+23x-6.5=0 | | 3x+6=2x+34 | | 3+6x=11+8x | | 2x+44=3y-9 | | 45=3(2x+7) | | m+2m+7m=60-5m | | 3+5x=10+3x | | 10v+23=93 | | 2x^2+64x+512=0 | | 7(d-5)+6= | | 2x^2+512=0 | | 3x-y(x+10)=9 | | z^2+2(1-i)z+2i=0 | | =1+3x | | x-6.1=5.3 | | 3x^5-14x^3-5x=0 | | -5k+2.7+2.4k+2.1k-5= | | 7x+4=19+2x | | h=24 | | 4x-(5x+5)=5x-47 | | y+1=-y+3 | | 3+5x=8+2x | | (x-y)*(4x-2y)= | | f(-x)=x^2-8x+9 | | 8x/3-3=29 | | (12x+3)+(-7x+5)= | | -2y-2.4+1.1-0.8y+2= | | w=-8/-7 |